Analisis Peluang, Tantangan, dan Strategi Industri Halal di Indonesia - Rina Samsiyah; Luluwatun Nazla; Silva Nur'aini; Frida Aprilya Saqina; Lina Marlina (Journal of Economics and Business, 2025)
Indonesia as a country with the largest Muslim population in the world, has great potential in the halal industry. The term "halal" refers to products and services that comply with Islamic teachings and are free from haram substances. The purpose of this study is to analyze the opportunities, challenges and strategies for the halal industry in Indonesia. The research methodology used is descriptive qualitative research. This research is a library research that uses secondary data obtained through scientific articles and other relevant documents. With the world's largest Muslim population, Indonesia should be the leading halal industry developer. However, according to the Indonesian Global Islamic Indicator 2020/2021, in fact, Indonesia is still the largest buyer of halal food in the world today. However, Brazil is the largest exporter of halal food. Given that the majority of Indonesia's population is Muslim, there is significant potential in the domestic market for halal goods. The Indonesian government has committed to encourage the growth of the halal industry. This is covered in various laws and regulations that have been made to ensure that halal products meet the national standards set by the halal authorities. ABSTRAK Indonesia sebagai negara dengan populasi Muslim terbesar di dunia, mempunyai potensi besar dalam industri halal. Yang dimaksud dengan “halal” adalah produk dan jasa yang sesuai dengan ajaran Islam dan bebas dari bahan haram. Tujuan dari penelitian ini adalah untuk menganalisis peluang, tantangan dan strategi industri halal di Indonesia. Metodologi penelitian yang digunakan adalah penelitian deskriptif kualitatif. Penelitian ini merupakan penelitian kepustakaan yang menggunakan data sekunder yang diperoleh melalui artikel ilmiah dan dokumen lain yang relevan. Dengan populasi Muslim terbesar di dunia, Indonesia seharusnya menjadi pengembang industri halal terkemuka. Namun menurut Indikator Islam Global Indonesia 2020/2021, nyatanya Indonesia masih menjadi pembeli makanan halal terbesar di dunia saat ini. Namun Brasil adalah eksportir makanan halal terbesar. Mengingat mayoritas penduduk Indonesia adalah Muslim, terdapat potensi besar di pasar domestik untuk barang-barang halal. Pemerintah Indonesia telah berkomitmen untuk mendorong pertumbuhan industri halal. Hal ini tercakup dalam berbagai peraturan perundang-undangan yang dibuat untuk memastikan produk halal memenuhi standar nasional yang ditetapkan oleh otoritas halal.